Analysis on English Speaking Performance: Exploring Students’ Errors and The Causes - Dayat Dayat (JETL (Journal of Education, Teaching and Learning), 2017)
This study was aimed to analyze students’ errors and the causes during speaking performance by twenty-nine fourth semester English students of in IKIP PGRI Pontianak who had low speaking performance. In collecting the data, video recordings were used to find errors and frequencies, while, focus group interview investigating factors of speaking errors. The data were analyzedby identifying the errors, grouping and tabulating into category codes. To analyze the interview, 1) listening to talking data, 2) shaping talking data, 3) communicating talking data with an interpretative intent, 4) reproducing or (re)constructing data, and building data credibility. The findings showed speaking errors with five categories: 28% of incorrect omissions, 26% of unnecessary words, 24% of misused forms, 19% of confused forms, and 3% of misplaced forms. Furthermore, other findings mostly included the causes of errors that influenced them in speaking were interlingual transfer, intralingual transfer, learning context, and communication strategies.